A Post-colonial Approach to Displacement and Home in “At the Border” by Choman Hardi (1974) and “Home” by Warsan Shire (1988) - Mariwan N. Hasan (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study examines the themes of displacement and home from post-colonial and psychological perspectives in two poems; “At the Border” by Choman Hardy (1974) and “Home” by Warsan Shire (1988). Both poems illustrate the harrowing experiences of refugees, emphasizing the emotional and psychological ramifications of compelled travel. This research employs a comparative analysis that merges post-colonial theory with psychological insights on trauma and identity, investigating how Hardy and Shire employ literary techniques, narrative voices, and symbolic representations to convey the intricacies of exile, belonging, and selfhood. The results indicate that both poets utilize vivid imagery and fractured structures to depict the dissolution of home and identity within the framework of post-colonial displacement. Hardy’s depiction of borderland pain underscores the political aspects of migration, illustrating the colonial legacy that influences the refugee experience, whereas Shire’s art accentuates the psychological anguish and communal longing for home. The study illustrates how both works contest Western notions of home and identity, providing a critical examination of the lasting psychological effects of colonialism on displaced individuals.